TINDAK TUTUR KIAI MENGENAI SYARAH (PENJELASAN) KITAB AL-HIKAM DAN TAFSIR Al-QUR’AN DALAM PENGAJIAN - Damayanti, Deasy Aditya (Universitas Pendidikan Indonesia, 2014)
This study is motivated by the notion that language is an important aspect in examining social life and culture. The use of language is realized through speech acts. However, the nature of the speech acts from the stand point of internal culture has many interpretations. According to Austin (1962), an etnopragmatic study is a study of speech acts that reveals an association between delivery of speech of the Kiai (the scholar) and the cultural values of the society. Therefore, this study seeks to capture the type of speech acts contained in the speech of Syarah (explanation) of Al-Hikam and Interpretation of the Koran recitation in a religious lecture for mothers in the Nurul Huda Mosque in Kampung Cireungit, Garut, and the relationship between the delivery of the speech and the cultural values of the society.